Unmet healthcare needs of adolescent girls: A study in Bangalore, in view of need-based hospital service planning - Thomas, Tincy, et al (ASCI: Journal of Management)
Adolescent health concerns of girls are an issue that hinders them from providing their best attempt in academics and resulting in a range of related disorders as well. This study attempts to explore the healthcare-seeking behaviours of Adolescent girls to determine their healthcare needs with a view to propose plans for hospital-based services. A community-based cross-sectional research was conducted among adolescent girls in age of 13 to 19 years in Bangalore. Descriptive and inferential statistics were applied for analysis. The chi-square method was used for testing the hypothesis at 0.5 level. The study shows that there are more than 40 percent of adolescent girls have growth and hormonal issues including menstrual problems. TB, Asthma, and other common health issues were next to this. Nutritional needs were unmet amongst the age category of 13 to 15. Almost half of them carry headache which is said to be'migraine'. The varied needs of adolescent girls such as nutritional, physical, hormonal, and menstrual should be addressed comprehensively in the adolescent-friendly clinics supported by a multidisciplinary team of experts.- Reproduced